MEASURING THE IMPACT OF OIL PRICE FLUCTUATIONS ON THE BUDGET DEFICIT - Malik bin Bashir bin Atiya Al-Wuraimi; Wissam Hussein Alwan (American Journals, 2023)
The relationship between oil prices and the public budget deficit is one of the most important topics and issues that have received the attention of economic researchers and have been widely discussed in both developing and developing countries alike. This research aims to analyze the relationship between the general budget deficit and oil prices and to show the impact of these variables on the general budget deficit in Iraq, and to measure that relationship by relying on the EVIEWS12 standard program. The stability test was used by applying the expanded Dickey-Fuller test and the cointegration test to discover a trend. The long-term relationship between these variables. The results of the research showed the inverse relationship between the price of crude oil and the general budget deficit in the long and short terms. The researcher recommended the need for the state and the competent authorities to focus in preparing the budget on all economic variables related to its budget, by comparing the budget for several years. In order to know the factors and variables affecting them and pay attention to them in order to raise the level of their revenues, and effective investment of Iraqi human capital, which is characterized by society’s vulnerabilities for those of working age, through providing job opportunities and developing workers’ productive skills in a way that achieves large returns for the general budget and represents a strong support link to pay It accelerates economic growth for all economic sectors, and its achieved returns are comparable to the returns of other physical and financial investments.
Keywords: Oil prices, budget deficit.